Recommendations Enhancing the Competitive Capacity of Small and Medium Enterprises after the Covid-19 Pandemic - Nguyen Van Tien (Emerging Science Journal, 2022)
In Vietnam, the Covid-19 pandemic has taken place since the beginning of 2020, has seriously impacted businesses' production and business activities, and pushed the world economy into recession. Like other countries globally, Vietnam has been severely affected by this global pandemic. During the Covid-19 outbreak, small and medium enterprises (SMEs) that stopped production or went bankrupt increased. Besides, due to the deep integration into the global value chain now closed to the port, the findings explored that SMEs with a larger scale faced many difficulties. The number of enterprises having to shrink production also increased rapidly. Most businesses say the Covid-19 outbreak has negatively affected their production and trade. The primary official data is distributed directly to business leaders through detailed questionnaires to collect preliminary data and selected models by a simple random process. SMEs failed to reach customers, broke the supply chain, revenue plummeted, and laid off many workers, so far struggling. The study objectives found that more than 87% of businesses are affected by Covid-19. Therefore, the article novelty had several recommendations for enhancing the competitive capacity of small and medium enterprises in Vietnam after the Covid-19 pandemic. Doi: 10.28991/esj-2022-SPER-09 Full Text: PDF